ProtoBandit: Efficient Prototype Selection via Multi-Armed Bandits - Roy Chaudhuri, Arghya; Jawanpuria, Pratik; Mishra, Bamdev (ACML 2022, 2022)
In this work, we propose a multi-armed bandit-based framework for identifying a compact set of informative data instances (i.e., the prototypes) from a source dataset S that best represents a given target set T. Prototypical examples of a given dataset offer interpretable insights into the underlying data distribution and assist in example-based reasoning, thereby influencing every sphere of human decision-making. Current state-of-the-art prototype selection approaches require O(|S||T|) similarity comparisons between source and target data points, which becomes prohibitively expensive for large-scale settings. We propose to mitigate this limitation by employing stochastic greedy search in the space of prototypical examples and multi-armed bandits for reducing the number of similarity comparisons. Our randomized algorithm, ProtoBandit, identifies a set of k prototypes incurring O(k|S|) similarity comparisons, which is independent of the size of the target set. An interesting outcome of our analysis is for the k-medoids clustering problem (T=S setting) in which we show that our algorithm ProtoBandit approximates the BUILD step solution of the partitioning around medoids (PAM) method in O(k|S|) complexity. Empirically, we observe that ProtoBandit reduces the number of similarity computation calls by several orders of magnitudes (100−1000 times) while obtaining solutions similar in quality to those from state-of-the-art approaches.